A nationwide survey on the management of the COVID-19 pandemic and respiratory disease in South Korea - Ang, Lin; Yim, Mi Hong; Song, Eunhye; Lee, Hye Won; Lee, Hyangsook; Kim, Tae-Hun; Willcox, Merlin; Hu, Xiao-Yang; Houriet, Joelle; Graz, Bertrand; Lee, Je-Won; Jang, Yunho; et al. (Frontiers in Medicine, 2022)
Background This study aimed to explore individual prevalence of respiratory symptoms and to describe the Korean population's treatment approaches, preventive health behaviors, and mental health conditions during the pandemic. Methods We analyzed responses from an online nationwide survey, conducted between February 2021 to May 2021, about people's experiences during the pandemic. Statistical analysis was also performed to see if there were any significant differences in treatment and prevention strategies between different groups of respondents (between those had respiratory symptoms, compared with those who did not, and between those tested positive for COVID-19, compared with those who did not). Results A total of 2,177 survey respondents completed the survey and, of these, only 142 had experienced symptoms. The most frequently reported respiratory infections related symptoms were runny or blocked nose (47.6%), cough (45.5%), fever (44.1%), sore throat (42.0%), and fatigue (30.1%). More than half of the respondents (53.1%) used complementary and alternative medicine (CAM) approaches as means of preventive measures. In terms of preventive behaviors, the more emphasized behaviors were mask-wearing (58.9%) and hand-washing after coming home (42.7%). The majority of the respondents (64.9%) did not show signs of mental health issues. Conclusion In South Korea, conventional medicine was mainly used for COVID-19 treatment whereas CAM was commonly used as preventive measures. COVID-19 was also found to have less impact on the general population's mental health. The findings of this study may shed light on how the pandemic impacted the general population.